Childhood trauma and malevolent creativity in Chinese college students: The chain mediation role of positive parenting and resilience - Li, Guyu; Zhu, Jingyao (Journal of Education and e-Learning Research, 2024)
This study explores the relationship between childhood trauma and malevolent creativity in college students and examines the chain mediation roles of positive parenting and resilience. Data is collected through survey questionnaires in a quantitative research approach. The SPSS macro-process 4.2 and SPSS 27.0 are used for data analysis. The sample consists of 860 participants from eight universities and vocational colleges across four provinces in China. The findings indicate that childhood trauma significantly predicts malevolent creativity in college students. Positive parenting and resilience mediate this relationship forming a chain mediation effect. Positive parenting enhances resilience which in turn reduces malevolent creativity. The results highlight the importance of positive parenting and improved resilience in mitigating the negative impacts of childhood trauma. This study confirms the significant influence of childhood trauma on malevolent creativity and highlights the chain mediation roles of positive parenting and resilience. The findings provide valuable insights for developing interventions to promote mental health and prevent malevolent behaviors among college students.